Exploring the implications of formal and informal social protection practices among the Afar communities in Ethiopia - Teka, Araya Mebrahtu; Weldu, Gabriel Temesgen (Archives of Business Research, 2018)
Evaluating the real impact of social protection instruments on social welfare is an important concern for governments, policymakers, and donors. This review explores social protection practices and the associated social institutional arrangements in the pastoral communities of Afar region, Ethiopia. Social capital in Ethiopia has involved different mechanisms and institutions and is implemented through various modalities. Traditional forms of social capital have made strong contributions, enabling people to mitigate crises. In the Afar community, the role of informal social networks is crucial and involves the sharing of food, animals and money during crises. Ethiopia’s Productive Safety Net Program (PSNP) has wider developmental aims, but its impact on pastoral communities has not gone beyond consumption smoothing. Climate change, which is associated with high rainfall variability, frequent drought and the fragile nature of the land, with serious degradation of natural resources, have presented severe problems for the pastoral community. And the effects are felt more by female-led households. The unequal treatment of women in social and economic affairs in these communities limits the ability of women to contribute to appropriate responses and adaptation. To cope with climate-related shocks, pastoralists pursue the traditional strategy of seasonal migration in search of pasture and water, and other strategies such as reducing the number of animals, selling of animals and herd diversification and conversion. Establishing efficient disaster prevention mechanisms, empowering women, enhancing local PSNP implementation capacity, strengthening and formalizing local networks, providing alternative employment and strengthening and introducing agricultural practices are all important in efforts to increase the effectiveness of the program, and complement efforts to improve pastoral livelihoods. JEL codes: I31, I38, P46, R11